Global Multimedia Value Chain Mapping Analysis of the Game League of Legends (2006-2025) - Calista, Swettie Ayu; Arrasikha, Ilmi; Putri, Nabilah Andiati; Purbantina, Adiasri Putri (Journal of Integrative International Relations, 2026)
This paper conducts a qualitative analysis of the Multiplayer Online Battle Arena game League of Legends, examining its Global Value Chain as defined by Riot Games and its interactions with external actors and companies worldwide throughout its creation and development. Online games continuously evolve across multiple aspects, and in many cases, their development involves not only internal teams but also collaborations with freelancers, partner studios, and other external companies. In the case of League of Legends, this results in a unique configuration of global partnerships, in which Riot Games coordinates multiple actors across production, localization, marketing, and esports operations. This paper draws on the Global Multimedia Value Chain theory to understand how global collaboration shapes the game’s production and its reception among players, providing a comprehensive picture of how Riot Games manages its internal operation alongside its external partnerships.